Effect of surfactants on encapsulation of hexadecane phase change material in calcium carbonate shell for thermal energy storage - Dixit, Prakhar (2022)
Microencapsulation of hexadecane core, an organic phase change material using inorganic calcium carbonate shell was carried out through self-assembly technique. The microcapsules prepared with mixed surfactants sodium dodecyl sulfate/non-polar polyvinylpyrrolidone (1:1 mass ratio) and core/shell of 1:1 mass ratio were found to produce spherical morphology observed from Field emission scanning electron microscope images. Fourier transform infrared analysis established no interaction between core and shell, while Energy dispersive X-ray spectrometer ensured presence of calcium carbonate. Latent heat of phase transformations, melting/crystallization temperatures, and encapsulation efficiency parameters were obtained from Differential scanning calorimetry, while Thermogravimetry analysis indicated the temperature range of its applicability. Latent heat of melting and corresponding encapsulation efficiencies estimated with varying core/shell mass ratios were between 59.48 J·g−1–95.92 J·g−1 and 26.85 %–43.12 %, respectively. Sample with equal amount of core/shell (1:1) was found to best microcapsules based on morphology and latent heat value. Encapsulation efficiency obtained from thermogravimetry analysis was consistent with those noted from differential scanning calorimetry. 100 thermal cycles (0 to 30 °C) indicated appreciable stability with temperature fluctuations, which may be useful as a cheap energy storage material in textile applications.